2008
DOI: 10.1590/s0104-66322008000400013
|View full text |Cite
|
Sign up to set email alerts
|

Ca alginate as scaffold for iron oxide nanoparticles synthesis

Abstract: -Recently, nanotechnology has developed to a stage that makes it possible to process magnetic nanoparticles for the site-specific delivery of drugs. To this end, it has been proposed as biomaterial for drug delivery system in which the drug release rates would be activated by a magnetic external stimuli. Alginate has been used extensively in the food, pharmaceutical and biomedical industries for their gel forming properties in the presence of multivalent cations. In this study, we produced iron oxide nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 22 publications
1
9
0
2
Order By: Relevance
“…The two most common methods are co-precipitation 51-53 and thermal decomposition 54,55 . Synthesis of SPIONs by co-precipitation of Fe 2+ and Fe 3+ in aqueous solutions has traditionally been the most utilized synthesis method 56 .…”
Section: Important Spion Design Parametersmentioning
confidence: 99%
“…The two most common methods are co-precipitation 51-53 and thermal decomposition 54,55 . Synthesis of SPIONs by co-precipitation of Fe 2+ and Fe 3+ in aqueous solutions has traditionally been the most utilized synthesis method 56 .…”
Section: Important Spion Design Parametersmentioning
confidence: 99%
“…A green synthetic strategy of oxide NPs (including magnetite) where starch was used as the stabilizing agent has been reported [22]. Alginates have been reported to act as a scaffold for the synthesis of magnetite NPs [23]. A modified chitosan (chitosan-polyacrylic acid) was used to improve the binding on magnetite NPs.…”
Section: Introductionmentioning
confidence: 99%
“…The Mossbauer spectrum ( Figure 3) was obtained which confirmed that Fe 3 O 4 had been successfully synthesized [32] with a paramagnetic doublet suggesting its superparamagnetic properties. [33][34][35][36][37] The broadening of the sextet lines reaffirms the superparamagnetic behaviour of the nanoparticles. The fitted parameter of the spectrum, isomer shift of 0.24(1) mm s −1 , is similar to that of magnetite nanoparticles.…”
Section: Characterization Of Catalystmentioning
confidence: 71%